Peningkatan Kapasitas Kader Kesehatan untuk Percepatan Integrasi Layanan Primer (ILP) dalam Pencegahan Balita Underwieght di Kota Tasikmalaya - Rian Arie Gustaman; Andik Setiyono; Meita Tyas Nugrahaeni; Wulan Tri Yutanti; Kharisma Nurul Fazrianti Rusman; Mohammad Ali Andrias; Dita Ali Destiati; Alika Arifiyani Ferbianti; Devina Tiara Safitri (Jurnal Abdimas Jatibara, 2026)
The 2022 SSGI results showed the prevalence of underweight toddlers in Indonesia was 17.1%, with West Java at 14.2%, and Tasikmalaya City at 13%. Data from the 2023 Health Office recorded 15,804 underweight toddlers (8.43%), with the highest number of cases occurring in the Karanganyar and Cibeureum Community Health Centers. This situation emphasizes the importance of increasing the capacity of integrated health post (Posyandu) cadres in the use of anthropometric tools to ensure more accurate nutritional data. The goal is to improve cadres' knowledge and skills in monitoring toddler growth and support the acceleration of Primary Service Integration (ILP). The activity method was carried out through socialization, training, and practical simulations using standard anthropometric tools (digital scales, infantometers, stadiometers, digital sphygmomanometers, and LILA tapes) with the assistance of a team of lecturers. The activities at the Harapan Bunda and Mekarsari Posyandus were attended by Posyandu cadres, representatives from the sub-district, neighborhood associations (RT), and community associations (RW). Participants showed high enthusiasm, were able to try using the tools independently, and were more confident in recording measurement results on the Child Health Card (KMS). This program is expected to produce more accurate nutritional data to support early detection and prevention of underweight.